ICE manual of bridge engineering - Parke, G. A. R.; Hewson, Nigel R. (ICE manuals., 2022)
"The ICE Manual of Bridge Engineering is the industry's leading guide to the engineering of all types of bridges. This book has been written by a team of leading experts and contains all of the key topics that any bridge engineer needs to refer to. All aspects from bridge design, materials and management of bridges to loadings, construction and accessories such as expansion joints, parapets and bearings are covered in this manual. Bridge inspections and economic and sustainable maintenance are also included. Fully updated to a third edition, this book features new chapters on bridge aesthetics and temporary works. It is aligned with the guidance given in the Eurocodes. This book will become your go-to authority on all aspects of bridge design, construction and management. Fully illustrated and with many examples of best practice, this book features chapters on: prestressed and reinforced concrete bridges; loads, load distribution and analysis; steel and aluminium bridges; arch bridges; suspension bridges; cable-stayed bridges; moveable and footbridges; repairing and strengthening; among other topics. The ICE Manual of Bridge Engineering will be of interest to all practitioners involved in any aspect of the analysis, design, construction, repair, inspection, maintenance, and refurbishment of bridges. It will also appeal to students at university or college, contractors, government agencies and research centres."--